Virtual reality as a non-medical tool in the treatment of anxiety, pain, and perception of time in children in the maintenance phase of acute lymphoblastic leukemia treatment - Velasco-Hidalgo, Liliana; González-Garay, Alejandro; Segura-Pacheco, Blanca Angélica; Esparza-Silva, Ana Luisa; Cuéllar Mendoza, Miguel Enrique; Ochoa-Drucker, Cecilia; Campos-Ugalde, Sofía; Bernabé-Gaspar, Luis Eduardo; Zapata-Tarrés, Marta (Frontiers in Oncology, 2024)
Management of pediatric cancer patients involves invasive procedures such a punctures, injections, catheter placements and chemotherapy which generate fatigue, nausea, vomiting, anxiety, and pain.Virtual Reality (VR) is a non-pharmacological intervention that is classified as a cognitive-behavioral method that relieves symptoms. We designed a cross-over protocol, included 20 patients between 9 and 12 years old, ten were male. All patients had acute lymphoblastic leukemia diagnosis and were treated with St. Jude's XV protocol in maintenance phase. Pain and anxiety were measured with validated scales in pediatric population. Despite we included a small group of patients, we found statistical difference in reduction of anxiety and perception of time. These results open a window to non-pharmacological treatments and show a strategy to improve quality of life in children inside the hospital.